PERBANDINGAN FRAMEWORK TOGAF DAN ZACHMAN DALAM IMPLEMENTASI ENTERPRISE ARCHITECTURE - Ramadhani, Citra; Padli Nasution, Muhammad Irwan (LPPM Universitas Bina Bangsa, 2024)
Enterprise Architecture (EA) is a framework that helps organizations integrate business strategies with information technology. Two popular frameworks in EA implementation are TOGAF (The Open Group Architecture Framework) and the Zachman Framework. This study aims to analyze the comparison between the TOGAF and Zachman frameworks, especially in the context of EA implementation in organizations. The methods applied in this study include literature studies and comparative analysis based on several important aspects, such as structure, focus, similarities, and implementation. The results of the study show that TOGAF focuses more on processes and continuous development, while Zachman emphasizes a more detailed classification framework and statistics. Both frameworks have their respective advantages; TOGAF excels in supporting innovation and adaptation, while Zachman is suitable for data consistency and consistency. By understanding these differences and advantages, organizations can choose the framework that best suits their needs and goals. This article is expected to provide insight for practitioners and researchers in determining an effective EA implementation strategy.